Link between hippocampus' raised local and eased global intrinsic connectivity in AD. Issue 5 (17th July 2014) - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Meng, Chun; Myers, Nicholas E.; Ortner, Marion; Mühlau, Mark; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Wohlschläger, Afra M.; et al.
Abstract: Background: The hippocampus (HP) is part of the default mode network (DMN), and both are key targets of Alzheimer's disease (AD). Because of widespread network degeneration, it has been suggested that increasing HP disconnection from the DMN may lead to progressive disinhibition of intra‐HP synchronized activity. Methods: To analyze HP local (i.e., within HP) and global (i.e., within DMN) intrinsic functional connectivity (local/global intrinsic functional connectivity [iFC]), healthy controls and patients with mild cognitive impairment and AD dementia were assessed by spatial high and normal resolution resting‐state functional magnetic resonance imaging. Results: Although patients' parietal local‐iFC was reduced and positively correlated with reduced global‐iFC within the DMN, HP local connectivity was progressively increased and negatively correlated with HP decreased global connectivity. Increased intra‐HP connectivity was associated with impaired memory. Conclusion: Our result demonstrates a link between increased local and reduced global hippocampal connectivity in AD. Increased intra‐HP synchrony may contribute to distinct symptoms such as memory impairment or more speculatively epileptic seizure.